Gene Mapping and Gene-Set Analysis for Milk Fever Incidence in Holstein Dairy Cattle - Pacheco, Hendyel A.; da Silva, Simone; Sigdel, Anil; Mak, Chun Kuen; Galvão, Klibs N.; Texeira, Rodrigo A.; Dias, Laila T.; Peñagaricano, Francisco (Frontiers in Genetics, 2018)
Milk fever is an important metabolic disorder that affects dairy cows around parturition. It is associated with a breakdown in the mechanisms of calcium homeostasis, resulting in very low blood calcium levels (hypocalcemia). The main objective of this study was to dissect the genetic basis underlying milk fever incidence in Holstein cattle. Data consisted of 31.6k producer-recorded lactation incidence records from 15.3k cows. The analysis included a whole-genome scan and a subsequent gene-set analysis in order to reveal individual genes, genetic mechanisms and biological pathways implicated in the incidence of periparturient hypocalcemia. The association analysis identified at least eight different genomic regions that explain considerable amounts of additive genetic variance for milk fever incidence. Notably, some of these regions harbor genes, such as CYP27A1, CYP2J2, GC, SNAI2 and PIM1, that are directly involved in vitamin D metabolic pathway. Moreover, the gene-set analysis revealed several functional terms, such as calcium ion binding, calcium ion transportation, T cell differentiation, B cell activation, protein phosphorylation, apoptosis, and protein kinase activity, among others, that could be implicated in the development of periparturient hypocalcemia. Overall, this comprehensive study contributes to a better understanding of the genetic control of this complex disease. In addition, these findings may contribute to the development of novel breeding strategies for reducing the incidence of milk fever in dairy cattle.